The impact of chronic obstructive pulmonary disease and hypertension on the development and progression of atrial fibrillation - L. D. Khidirova; D. A. Yakhontov; S. A. Zenin; T. S. Kuropii (Кардиоваскулярная терапия и профилактика, 2019)
The article presents a review of the literature, reflecting ideas about the effect of chronic obstructive pulmonary disease on the development and progression of atrial fibrillation. Modern concepts regarding the substrate and triggers of paroxysms of atrial fibrillation have recently changed significantly. The role of concomitant diseases, in particular arterial hypertension and chronic obstructive pulmonary disease, formed the basis for changes in the electrophysiological properties of the myocardium.